Sustainable design strategies for fashion postproduction (ModaPalavra e-periódico, 2020)
Originated in a doctoral dissertation, this study proposes a set of strategies for the post-production of fashion products, focusing on the stages of communication, sale, distribution, follow-up of the consumer experience, reverse logistics and end-of-life procedures. The proposed strategies seek to expand the performance of designers and companies on the final stages of the product life cycle, considering them as part of the sustainable fashion project.Keywords: sustainable design strategies, post-production, fashion product.
Keywords: design strategies; post-production; fashion product